Effectiveness of Development LKS Based on International Program for Student Assessment (PISA) with Realistic Learning For Improving Mathematical Communication Skills of Student of MTsN 2 Medan - Hanizar Sary; Hasratuddin Hasratuddin; Edy Surya (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study discusses about the Effectiveness of Development LKS Based on International Program for Student Assessment (PISA) with Realistic Learning For Improving Mathematical Communication Skills of Student of MTsN 2 Medan. This research is conducted in MTsN 2 Medan which is located on Paratun street No. 3 Medan Estate in even semester TP. 2017/2018. The reason for choosing this school because; 1) in MTsN 2 Medan no one has ever conducted research on developing student worksheets (LKS) with Pisa-based instruments namely Mathematical Literacy with Realistic learning, 2) the unavailability of Mathematics literacy worksheets with Realistic learning, 3) The approach adopted by the teacher has not leads to Mathematics literacy, 4) the importance of mathematical communication skills of MTs students to improve the mathematical abilities of MTsN 2 Medan. The result shows that Achieving learning objectives ≥ 65% and Classical Provisions ≥ 85% Learning time with Realistic Approaches ≤ time with ordinary learning. Student responses to the positive learning component. The level of achievement of students' mathematical communication skills is an increase in Student Communication Ability through LKS which is developed based on PISA with Realistic learning